Geotechnical Assessment of Cement Kiln Dust-Stabilized Black Cotton Soil for Subgrade Improvement in Road Construction - Selnan, Jingnap Princewill; Binkam, Iddo Sharon; Yusuh, Abdulkarim Albdullahi (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study explores the effectiveness of Cement Kiln Dust (CKD) as a stabilizing agent for black cotton soil to enhance its performance as a subgrade material in road construction. Laboratory experiments were conducted to assess the California Bearing Ratio (CBR) and Unconfined Compressive Strength (UCS) of both untreated and CKD-stabilized soils, with CKD incorporated at varying proportions ranging from 0% to 15%. The results revealed a significant improvement in both CBR and UCS values with increasing CKD content, peaking at 12.5%, where the stabilized soil achieved a CBR ≥ 10% and UCS ≥ 100 kN/m². These enhancements are attributed to pozzolanic reactions, reduction in soil plasticity, and effective void filling facilitated by CKD. However, strength values declined beyond the 12.5% threshold, likely due to excessive fines disrupting particle packing efficiency. The 12.5% CKD mix not only satisfied standard subgrade strength criteria but also exhibited improved durability under saturated conditions, identifying it as the optimal stabilization level. The findings support the use of CKD as a sustainable and cost-effective solution for black cotton soil stabilization. Further research is recommended to assess long-term performance under actual traffic loads and environmental conditions.